Biomarker Discovery of Pancreatic and Gastrointestinal Cancer by 2DICAL: 2-Dimensional Image-Converted Analysis of Liquid Chromatography and Mass Spectrometry. (10th July 2012) - Ono, Masaya; Kamita, Masahiro; Murakoshi, Yusuke; Matsubara, Junichi; Honda, Kazufumi; Miho, Banno; Sakuma, Tomohiro; Yamada, Tesshi
Abstract : Biomarkers tested by blood sample are of great use to clinicians as they provide useful information to aid an early and accurate diagnosis. Comprehensive "omics" studies are expected to facilitate the identification of such new biomarkers, and much research is being performed in this area. Our proteomics analysis system of 2-dimensional image-converted analysis of liquid chromatography and mass spectrometry (2DICAL) has successfully identified several new blood biomarkers from the clinical blood samples of pancreatic and colorectal cancer patients.